ВПЛИВ ДЕЦЕНТРАЛІЗАЦІЇ НА СТРУКТУРУ ТА ДИНАМІКУ ДОХОДІВ І ВИДАТКІВ МІСЦЕВИХ БЮДЖЕТІВ - Марчук, Анна Павлівна (Науковий журнал «Світ фінансів», 2018)
Марчук А. П. Вплив децентралізації на структуру та динаміку доходів і видатків місцевих бюджетів. Досліджено практичні аспекти застосування податково-бюджетних інструментів забезпечення виконання місцевими бюджетами покладених на них суспільно важливих функцій. З метою визначення змін у структурі та співвідношеннях фінансування видаткових повноважень і виявлення тенденцій щодо ролі дохідних інструментів у наповненні місцевих бюджетів у процесі бюджетної децентралізації, проаналізовано видатки і доходи місцевих бюджетів Тернопільської області протягом 2004–2017 рр., здійснено порівняння із тенденціями по Україні. Встановлено, що через сповільнене економічне зростання і систематичне зниження частки власних доходів обсяги фінансування закладів та заходів соціально-культурної сфери останніми роками зазнали скорочення. Обґрунтовано, що за сучасних умов для підвищення ефективності надання суспільних послуг за рахунок місцевих бюджетів необхідно активізувати реформи із удосконалення податково-бюджетних інструментів фінансового забезпечення місцевого самоврядування та розробити цілісну концепцію із економічно обґрунтованими та взаємоузгодженими заходами впливу на всі сфери соціально-економічного життя держави. Марчук А. П. Влияние децентрализации на структуру и динамику доходов и расходов местных бюджетов. Исследованы практические аспекты применения налогово-бюджетных инструментов обеспечения выполнения местными бюджетами возложенных на них общественно важных функций. С целью обнаружения изменений в структуре и соотношениях финансирования расходных полномочий и определения тенденций в изменении роли доходных инструментов в наполнении местных бюджетов в процессе бюджетной децентрализации, проанализированы расходы и доходы местных бюджетов Тернопольской области в течение 2004–2017 гг., проведено сравнение с тенденциями по Украине. Установлено, что в связи с замедленным экономическим ростом и систематическим снижением доли собственных доходов в последние годы объемы финансирования учреждений и мероприятий социально-культурной сферы подверглись сокращению. Обосновано, что в современных условиях для повышения эффективности предоставления общественных услуг за счет местных бюджетов необходимо активизировать реформы по совершенствованию налогово-бюджетных инструментов финансового обеспечения местного самоуправления и разработать целостную концепцию с экономически обоснованными и взаимосогласованными мерами воздействия на все сферы социально-экономической жизни государства. Marchuk A. Influence of decentralization on structure and dynamics of income and expenditures of local budgets. Introduction.The objective reason for the existence of an institution of local budgets is an increase in the efficiency of the provision of public services guaranteed by the state due to the proximity of such services to the immediate consumer. This process is based on the principle of subsidiarity, requires a sufficient level of financial security of local budgets and demonstrates the basic idea of the concept of fiscal decentralization. The decentralization reform is systematic and involves structural changes in various spheres of public life. The object of research of this article is the impact of changes in tax and budget laws aimed at decentralization on structure and dynamics of income and expenditures of local budgets. Purpose.The purpose of the article is to identify trends, priorities and unresolved issues in financing local budget expenditures, compare dynamics of expenditures with dynamics and structural changes in local budget revenues. Results. In the course of the research, the expenditures and revenues of local budgets of Ternopil region during 2004-2017 were analysed, comparison with trends in Ukraine was made. It has been established that due to slowed down economic growth and a systematic decrease in the share of own revenues in recent years, the amount of funding for institutions and activities in the social and cultural sphere has been reduced and the transfer of important functions to the local level was not accompanied by the transfer of sufficient amount of financial resources. Conclusions.The strategic goal of decentralization is to ensure the availability and proper quality of public services for all categories of the population. The decentralized budget system should function on the basis of a coordinated, unified national cooperation policy for many independent institutions, each of which has a legislatively defined sphere of autonomy. Since tax revenues form the main volume of own revenues of local budgets, the issue of improving the efficiency of tax administration comes to the forefront in the context of decentralization changes. Therefore, on the way to ensuring the increase of tax revenues, the strategic goal of local authorities should be to promote economic development of regions.